2014
DOI: 10.1159/000358872
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Standard for Cavernous Sinus Hemangiomas: Proposal for a Diagnostic Test

Abstract: Background: By definition, a cavernous sinus is a vascular plexus. A hemangioma is a vascular tumor which is rich in vascular plexus and caused by vascular deformity or tumor-like proliferation. Radiosurgery can effectively control the growth of smaller cavernous sinus hemangiomas (CSHs). This paper aimed to quantify the MRI characteristics of CSHs which provided a basis for further treatment. Methods: A retrospective analysis was conducted of the MRI characteristics of 133 cavernous sinus lesion patients betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Since the 1990s, the characteristic appearance of CaSHs on MR images has been described in many studies, which greatly [8]. Some CaSHs are characterized by their progressive enhancing process from heterogeneous to uniform or 'edge-tocenter' enhancement on dynamic MRI, which is similar to hepatic hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1990s, the characteristic appearance of CaSHs on MR images has been described in many studies, which greatly [8]. Some CaSHs are characterized by their progressive enhancing process from heterogeneous to uniform or 'edge-tocenter' enhancement on dynamic MRI, which is similar to hepatic hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1999 when Iwai et al demonstrated a favorable case of GKS for a postsurgical CaSH [10], many studies have reported similar treatment outcomes of GKS for residual CaSHs after surgery [2,9,13,16,21,24,28,31,35]. They also noted the radiological characteristics of these tumors, especially their extremely high signal on MR T2-weighted and FLAIR sequence images, which have greatly improved the diagnosis of these tumors before operation [2,8,12,16,17,19,36]. At present, radiosurgery is being used and becoming a promising option for primary or postoperative management of patients with CaSHs.…”
Section: Introductionmentioning
confidence: 93%
“…Figure 4). Therefore, these sequences are considered the most significant reference among all types of slices in the differential diagnosis of the two studied tumor types (23,24). The tumor classification model trained by the transverse T1-weighted contrast-enhanced sequence images and tested on the external validation sets achieved high accuracy, sensitivity, and specificity in automated cavernous hemangioma and schwannoma differential diagnosis in a real-world setting that is completely consistent with the clinical environment.…”
Section: Resultsmentioning
confidence: 92%
“…( 1234567890 www.nature.com/scientificreports/ Radiomics can provide additional metabolic and biological information in addition to the traditional MRI metrics. Gray contrast, uniformity, depth, and texture roughness have been used to study tumor grading, prediction of genomic information, and differentiation of lesion and non-lesion images [39][40][41] . The present study found that higher-order features could better reflect the degree of tumor heterogeneity and texture information.…”
Section: Discussionmentioning
confidence: 99%